Collaborative evaluative proposal between two departments of the Early Childhood Education program in Chile for the development of academic and professional competencies using an alternative assessment - Contreras Paredes, Norton (2025)
The presented systematization accounts for an evaluation instance applied between two departments of the Early Childhood Education program at a Chilean university. The objective was to assess the implementation of an alternative evaluative experience based on competencies in a discussion format. The characteristics of the sample group included 32 students from the Early Childhood Education program at a private higher education institution in Santiago, Chile, who were simultaneously taking the courses in Neuroeducation and Developmental Psychology. Their choice was a non-probability convenience sample, as the researchers had easy access to the participating subjects given the circumstances. One group of students was required to orally present a topic related to both courses and then make comments and ask questions about a different topic presented by another group. The instance was evaluated using a rubric-type instrument (regarding both form and content) with a requirement of 70% on the Chilean grading scale. It was found that the students achieved 67% of the learning indicator related to elements of form and 100% of the learning indicators related to elements of content. Thus, it is proposed that there is a need to generate more and better evaluation instances that differ from traditional written assessments in higher education, strengthening a curriculum oriented toward competencies and focused on adequate professional and labor performance.